2017
DOI: 10.1002/pssa.201700269
|View full text |Cite
|
Sign up to set email alerts
|

Tunable white light emission from hafnium oxide films co‐doped with trivalent terbium and europium ions deposited by Pyrosol technique

Abstract: In this paper, the photo and cathodoluminescent properties of HfO2 films optically activated with different atomic concentrations of Tb3+ and Eu3+ ions, deposited by the Pyrosol technique, are reported. These films were deposited at temperatures from 400 to 600 °C, using chlorides as raw materials. The surface morphologies of all deposited films were rough and dense. X‐ray diffraction analysis showed that the films deposited at 600 °C were polycrystalline exhibiting the HfO2 monoclinic phase. The tuning by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When photo-and cathodoluminescence in the samples under study were measured, a blue-green emission was observed at different temperatures (see Figure 4). This is characteristic of hafnia in various morphological modifications such as thin films [6,23,42,45], nanopowders [7,46,47], nanocrystals [48,49], and bulk single crystals [44]. It should be noted that cooling the nanotubes to a temperature of 10 K has almost no influence on the broad Gaussian-shaped bands on the PL spectra (see inset in Figure 4).…”
Section: Spectral Characteristics Of Luminescencementioning
confidence: 91%
See 1 more Smart Citation
“…When photo-and cathodoluminescence in the samples under study were measured, a blue-green emission was observed at different temperatures (see Figure 4). This is characteristic of hafnia in various morphological modifications such as thin films [6,23,42,45], nanopowders [7,46,47], nanocrystals [48,49], and bulk single crystals [44]. It should be noted that cooling the nanotubes to a temperature of 10 K has almost no influence on the broad Gaussian-shaped bands on the PL spectra (see inset in Figure 4).…”
Section: Spectral Characteristics Of Luminescencementioning
confidence: 91%
“…Conducting experimental research on the optical and luminescent properties of HfO 2 NTs is extremely important for establishing the aspects of their energy spectrum caused by the morphology of the material. Currently, independent investigations of the optical and luminescent properties of bulk and thin-film hafnia samples doped with various ions, mainly with an amorphous and monoclinic structure, have been undertaken [8,19,[21][22][23][24][25]. Simultaneously, examining the developed surface structures of hafnia could provide insight into the role of surface optically active centers and defects of various natures in the radiative and non-radiative relaxation processes of electronic excitations in HfO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…QE around 35% and 25% were obtained using excitation wavelengths of 204 nm for Tb 3+ and 215 nm for Eu 3+ , respectively. HfO 2 films co-doped with Tb 3+ and Eu 3+ ions were synthesized at substrate temperatures from 400 to 600 °C using chlorides as reactive source materials [93]. These films became polycrystalline at 600 °C exhibiting the HfO 2 monoclinic phase.…”
Section: Luminescent Materialsmentioning
confidence: 99%
“…HfO 2 films are susceptible to doping with different rare earths, emitting at different colors depending on the dopant when excited with UV light. Crystallinity allows the incorporation of this type of ions [12]. The most common precursors used to synthesize HfO 2 are chlorides and metal-organics.…”
Section: Introductionmentioning
confidence: 99%